2018
DOI: 10.1042/bsr20180712
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment for miRNA polymorphisms in hepatocellular cancer risk: a systematic review and meta-analysis

Abstract: MiRNA polymorphisms had potential to be biomarkers for hepatocellular cancer (HCC) susceptibility. Recently, miRNA single nucleotide polymorphisms (SNPs) were reported to be associated with HCC risk, but the results were inconsistent. We performed a systematic review with a meta-analysis for the association of miRNA SNPs with HCC risk. Thirty-seven studies were included with a total of 11821 HCC patients and 15359 controls in this meta-analysis. We found hsa-mir-146a rs2910164 was associated with a decreased H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…However, patients with CC or CG genotypes of rs2910164 were more susceptible to the other cancers. At the same time, three large meta-analyses found that the CC genotype was associated with a decreased risk of cervical, hepatocellular, and prostate cancer [ 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with CC or CG genotypes of rs2910164 were more susceptible to the other cancers. At the same time, three large meta-analyses found that the CC genotype was associated with a decreased risk of cervical, hepatocellular, and prostate cancer [ 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis for miR-196 included only two studies, with the following HR results (HR = 0.28, 95% CI: 0.15–0.52, p < 0.001; I 2 = 0%, p = 0.950, n = 197) [ 43 ]. In addition, there were three meta-analyses on miR-196a polymorphism as a risk of developing cancer [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the hsa-mir-146a residing rs2910164 (G to C variation) was linked to reduced HCC risk for the C allele while hsa-mir-34b/c rs4938723 (T to C variation) was associated with increased HCC risk. Furthermore, hsa-mir-196a-2 rs11614913 and hsa-mir-149 rs2292832 variations were all correlated with elevated HCC risk [319].…”
Section: Utilizing Non-coding Variants In Clinomicsmentioning
confidence: 92%